The Journey towards Integrated Reporting in Bangladesh - Nakib, Mohammad; Dey, Pappu Kumar (Asian Economic and Financial Review, 2018)
The necessities of cohesive, integrated and decision-supportive information for apprehending the future prospect and capacity of the companies have led to the advent of integrated reporting (). This study examines whether the Bangladeshi companies are moving towards . The extent of practices of the listed companies in Bangladesh for the year 2014 to 2016 has been measured with a view to reaching a conclusion. In regard to this study, DSE30 companies have been considered as the sample companies while their integrated reports or, in absence, their annual reports have been scrutinized. Content analysis approach has been followed in this study to construct index considering the fifty items of the eight content elements of as prescribed by International Integrated Reporting Council in its International Framework. Our analysis exhibits that in 2016, 22% of the sample companies have adopted , which has been commenced in 2015 whereas no company has undertaken in the year 2014. Content-wise index depicts that the disclosures of items under each of the content elements have been increasing over the time. Item-wise analysis has demonstrated some items of (i.e. materiality determinations process, linkage between strategy and resource allocation plan), disclosures of which have been appeared in the annual reports after the adoption of . Company-wise ensures that index for each company has been either increasing or remaining the same over the period. In total, index for all the sample companies has increased to 0.6148 from 0.4511 over the three years. These indicate that companies in Bangladesh have started adopting through standalone integrated report or annual report in an integrated way in spite of having no mandatory requirement.